2016
DOI: 10.1021/acs.jpcc.6b09781
|View full text |Cite
|
Sign up to set email alerts
|

Temperature- and Size-Dependent Compositionally Tuned Microstructural Landscape for Ag-46 Atom % Cu Nanoalloy Prepared by Laser Ablation in Liquid

Abstract: We report a temperature- and size-dependent compositionally tuned microstructural landscape for Ag-46 atom % Cu alloy nanoparticles. The microstructural and morphological changes were established through the technique of in situ transmission electron microscopy. The nanoparticles were synthesized by laser ablation of alloy target in an aqueous medium. The as-synthesized particles predominantly contain nanosized grains of a single-phase solid solution with grains having sizes ∼3 ± 0.5 nm. For particles with sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 64 publications
1
15
0
Order By: Relevance
“…In an approximate sense, a mixture of Ag and Cu bimetallic NPs, with a nanograin microstructure, can be considered a single-phase nanoalloy ( Figure 11 a), whereas, in other microstructures, such as in Figure 11 b,c, the Ag and Cu atoms do not distribute uniformly. It was found that homogenous AgCu nanoalloys ( Figure 11 a) gradually separate phases ( Figure 11 b–d), as the temperature is increased [ 254 ]. In addition to the influence of temperature, the morphologies of the Cu-rich α phase and the Ag-rich β phase can change with an increase of Cu content, passing from separated phases to nanograins to core-shell microstructures ( Figure 12 a–d), since the microsystems tend to keep the α-β interphase surface energy minimum [ 237 , 255 ].…”
Section: Mixed Ag–cu Nps and Agcu Nanoalloysmentioning
confidence: 99%
See 1 more Smart Citation
“…In an approximate sense, a mixture of Ag and Cu bimetallic NPs, with a nanograin microstructure, can be considered a single-phase nanoalloy ( Figure 11 a), whereas, in other microstructures, such as in Figure 11 b,c, the Ag and Cu atoms do not distribute uniformly. It was found that homogenous AgCu nanoalloys ( Figure 11 a) gradually separate phases ( Figure 11 b–d), as the temperature is increased [ 254 ]. In addition to the influence of temperature, the morphologies of the Cu-rich α phase and the Ag-rich β phase can change with an increase of Cu content, passing from separated phases to nanograins to core-shell microstructures ( Figure 12 a–d), since the microsystems tend to keep the α-β interphase surface energy minimum [ 237 , 255 ].…”
Section: Mixed Ag–cu Nps and Agcu Nanoalloysmentioning
confidence: 99%
“… ( a ) Single-phase AgCu solid solution; ( b ) core-shell structure of AgCu nanoalloys; ( c ) structure of Ag and Cu in both phases; ( d ) biphasic. Reproduced with permission from Reference [ 254 ]. Copyright 2016, American Chemical Society.…”
Section: Figurementioning
confidence: 99%
“…During continued heating, the NPs eventually coarsened to several hundred nanometers in size through coalescence. In contrast, when Cu-Ag NPs of near-equiatomic composition produced by pulsed laser deposition 19 were exposed to temperatures up to 600 °C, the initially homogeneous solid solution phase decomposed to form Ag-and Cu-rich phases. Figure 1, which is reproduced from this work 19 , shows that particles below ∼20 nm in size developed into a Janus configuration, while the larger ones (size ∼40 nm) exhibited an Ag@Cu CS morphology.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, bulk thermodynamics favors phase separation in the NPs and suppresses formation of homogeneous alloyed phase. However, capillary forces come into dominance at small sizes, and depending on the composition, size, and method of preparation, NPs are sometimes found in the homogeneous alloyed state as well 17,19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a hydrophilic coating removes dust by spreading water on the surface instead of forming water droplets on the surface. This method allows water droplets to spread between pollutants and the substrate surface, thereby removing the pollutants to be attached to the substrate and letting them flow with water droplets [12][13][14][15][16]. The water-soluble polymer materials TiO 2 and silica are known to have excellent hydrophilicity [17].…”
Section: Introductionmentioning
confidence: 99%